Discursive construction of social selfhood: an analysis of North Korean elementary moral education textbooks. Issue 4 (4th July 2022) - Jang, Soo Bin
ABSTRACT: This study critically analyzes North Korean elementary moral education textbooks published under the Kim Jong-un regime to understand how identities and power are enacted through school curricula. In order to interpret North Korean elementary moral education textbooks, the study reviews a brief history of compulsory moral education in East Asia in the context of Korean ethnonationalism. Three main themes emerge regarding the construction of North Korean sense of self, namely 'fabricating ethnic homogeneity', 'correct attitude towards a new supreme leader', and a 'formally systemized mode of living'. Such findings uncover that the state's institutionalized manufacturing of regime adherence begins at an early age and meticulously shapes individuals' world views. The implications of the politics of monocultural, ethnonational identity formation are discussed.